Determinants of wheat trade, 1999-2008 - Johnson, Jessica Jo (Kansas State University, 2011)
This research will identify and quantify the determinants of international wheat trade from 1999-2008. This study will focus on the following objectives: (1) Review literature on international wheat trade to develop a suitable conceptual model (2) Quantify the impact of economic variables including price, income, exchange rates, transportation costs, and trade policies; and (3) Extend previous work by further consideration of trade policies and international relationships. Regression results indicate that economic factors continue to play a major role in wheat trade. Domestic price had the largest level of statistical significance of non-trade agreement factors in this analysis. The regression results highlight that national income, distance between nations, exchange rate, inflation and respective populations are also important in determining the flow of wheat. Openness to trade and agriculture production variables were statistically significant, demonstrating the commodity nature of wheat trade. Sharing a common border and language are also positive factors in wheat trade. Colonial heritage does have some small impacts, negative for direct colonies and positive for nations sharing a common colonizer. This analysis extends previous international wheat trade research through the inclusion of multilateral relationships and bilateral trade agreements. This study showed that not being a member of the WTO is a positive factor in the trade of wheat. The review of trade agreements added depth to this study by examining both trade creation and trade diversion for each agreement specifically for their effects on wheat trade. The estimated models show that nations which develop agreements with contrasting qualities from themselves are likely to see higher gains from free trade agreements. However, when nations engage in agreements with nations in a similar location or income structure, trade diversion iv occurs. The analysis also shows that trade agreements can overcome factors that may have a negative impact on the trade of wheat such as distance or colonial relationships. By understanding the determinants of wheat trade, players in the wheat market can create a more transparent and fluid trading system.
Keywords: Agriculture economics; Agriculture, General (0473)